EUS is superior to secretin-enhanced cholangio-MRI to establish the etiology of idiopathic acute pancreatitis - Vila, Juan J.; Mendioroz, F. Javier Jiménez; Yeaton, Paul; Fernández-Urién, Iñaki; Sanchotena, José Luis García; Goñi, Silvia; Alonso, Marta Gómez; Carrascosa, Juan; Borda, Ana; Prieto, Carlos; Urman, Jesús; Zozaya, José M (Endoscopy International Open, 2020)
Background and study aims The etiology of idiopathic acute pancreatitis (IAP) should always be defined. Our aim was to compare the diagnostic value of endoscopic ultrasound (EUS) versus secretin-enhanced magnetic resonance cholangiopancreatography (S-MRCP) in patients with IAP. Patients and Methods Patients admitted to a single tertiary care University hospital with IAP were invited to participate in the study. Enrolled patients underwent EUS and S-MRCP in a single-blinded comparative study. EUS and S-MRCP were performed no sooner than 4 weeks after discharge. The diagnostic yield of EUS and S-MRCP and demographic variables were included in the analysis. Additional follow-up, results of subsequent serology, radiographic exams, and relevant histological analysis were considered in determination of the final diagnosis. Results A total of 34 patients were enrolled; EUS was normal in six, cholelithiasis was defined in 15, choledocholithiasis in two, pancreas divisum in three, branch-type intraductal papillary mucinous tumor (IPMT) in three, and chronic pancreatitis in five. S-MRCP identified choledocholithiasis in one, divisum in four, branch-type IPMT in three, chronic pancreatitis in two; 24 subjects diagnosed as normal by S-MRCP. Diagnostic correlation between EUS and S-MRCP was slight (kappa = 0.236, 95 % confidence interval: 0.055–0.416). EUS provided a statistically significantly higher diagnostic yield than S-MRCP: 79.4 % (CI95 %: 65 %–94 %) vs 29.4 % (CI95 %: 13 %–46 %) (P = 0.0002). The sensitivity, specificity, and positive and negative predictive values of EUS and S-MRCP were 90 %, 80 %, 96 %, 57 % and 33 %, 100 %, 100 % and 16 %, respectively. Conclusion The diagnostic yield of EUS is higher than S-MRCP in patients with IAP.